Exploring the intersection of Torajan hanging graves and physics concepts in ethnoscience education - Nurul Arsyi; Muh. Mahfud; Nurul Hidayah; Mutahharah Hasyim; Risky Setiawan (Momentum: Physics Education Journal, 2026)
This qualitative, ethnographic study aims to identify, analyze, and reconstruct the physics principles embedded in the Hanging Grave tradition of Tana Toraja, specifically focusing on the erong (coffin), body, and hanging structures into contextual learning materials. Conducted in Kesu District, Toraja Regency, data were gathered via triangulation (observations, interviews, and documentation) utilizing purposive sampling. Four key informants participated: a traditional chief, a coffin manufacturer, a cemetery caretaker, and a community member. Data were processed through reduction, display, and verification. The study reveals three major socio-cultural physics applications that are (1) Static Equilibrium, The erong support system on the cliff wall functions as a cantilever beam. The static load is sustained by a pinch moment at the beam's base, satisfying static equilibrium criteria to prevent rotation or collapse. (2) Kinematics and Dynamics, The Ma'Popengkalo Alang (body transportation) ritual involves mechanical work (W = F.s) and energy transformations. The minimum force required to move the mass vertically is heavily dictated by the cliff's angular slope. (3) Thermodynamics, The degradation of erong wood follows thermodynamic and thermal expansion principles. Periodic ambient temperature fluctuations induce thermal stress, accelerating weathering. This is culturally mitigated through physical conservation during the Ma'nenek ceremony. Ultimately, this indigenous science reconstruction successfully transforms complex cultural engineering into structured, contextual physics concepts ready for curriculum integration.